Edukasi Strategi Bisnis BUMDes Berbasis Revitalisasi-Optimalisasi dan Canvas Business Model - Andriyanto, Dicky; Utama, Anak Agung Gde Satia; Solikhah, Tridiganita Intan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2022)
Relevant business models can improve the performance of BUMDes managers to be more active to encourage the rural economy. Partners who participated in this activity included the Tangunan Village BUMDes manager and village residents. The problem that occurs with partners is the role of BUMDes which has not been maximized in managing resources in the village and its managerial capabilities are still conventional. This service activity is carried out through seminars and discussions with academics. The results of the activity showed that participants were enthusiastic about participating in the activities as evidenced by their activeness in delivering the material and a good level of understanding through increasing test results before and after delivering the material.